Cryptic diversity and spatial genetic variation in the coral Acropora tenuis and its endosymbionts across the Great Barrier Reef. (7th July 2022) - Matias, Ambrocio Melvin A.; Popovic, Iva; Thia, Joshua A.; Cooke, Ira R.; Torda, Gergely; Lukoschek, Vimoksalehi; Bay, Line K.; Kim, Sun W.; Riginos, Cynthia
Abstract: Genomic studies are uncovering extensive cryptic diversity within reef‐building corals, suggesting that evolutionarily and ecologically relevant diversity is highly underestimated in the very organisms that structure coral reefs. Furthermore, endosymbiotic algae within coral host species can confer adaptive responses to environmental stress and may represent additional axes of coral genetic variation that are not constrained by taxonomic divergence of the cnidarian host. Here, we examine genetic variation in a common and widespread, reef‐building coral, Acropora tenuis, and its associated endosymbiotic algae along the entire expanse of the Great Barrier Reef (GBR). We use SNPs derived from genome‐wide sequencing to characterize the cnidarian coral host and organelles from zooxanthellate endosymbionts (genus Cladocopium ). We discover three distinct and sympatric genetic clusters of coral hosts, whose distributions appear associated with latitude and inshore–offshore reef position. Demographic modelling suggests that the divergence history of the three distinct host taxa ranges from 0.5 to 1.5 million years ago, preceding the GBR's formation, and has been characterized by low‐to‐moderate ongoing inter‐taxon gene flow, consistent with occasional hybridization and introgression typifying coral evolution. Despite this differentiation in the cnidarian host, A. tenuis taxa share a common symbiont pool, dominated by the genus Cladocopium (Clade C). Cladocopium plastid diversity is not strongly associated with host identity but varies with reef location relative to shore: inshore colonies contain lower symbiont diversity on average but have greater differences between colonies as compared with symbiont communities from offshore colonies. Spatial genetic patterns of symbiont communities could reflect local selective pressures maintaining coral holobiont differentiation across an inshore–offshore environmental gradient. The strong influence of environment (but not host identity) on symbiont community composition supports the notion that symbiont community composition responds to habitat and may assist in the adaptation of corals to future environmental change.